2023
DOI: 10.7759/cureus.38762
|View full text |Cite
|
Sign up to set email alerts
|

Computer Vision Syndrome Among Medical Students at the University of Khartoum, Sudan: Prevalence and Associated Factors

Abstract: Background and aims Regular continuous uninterrupted use of electronic devices, such as smartphones, tablets, and computers, can result in a spectrum of vision-related symptoms known as computer vision syndrome. Students today can readily access information and books on their smartphones and computers, which reduces their reliance on printed texts. Numerous muscle-related and ocular complaints could arise from this. The primary objective of this study was to estimate the prevalence of computer visio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 29 publications
4
4
1
Order By: Relevance
“…Regarding CVS-associated factors, our results highlighted the importance of screen distance and the use of screen filters, both significantly associated with CVS development. These findings align with previous research 19 , 23 , although the efficacy of screen filters in reducing CVS prevalence has been debated 19 , 24 .…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Regarding CVS-associated factors, our results highlighted the importance of screen distance and the use of screen filters, both significantly associated with CVS development. These findings align with previous research 19 , 23 , although the efficacy of screen filters in reducing CVS prevalence has been debated 19 , 24 .…”
Section: Discussionsupporting
confidence: 91%
“…Compared to previous studies which reported a wide prevalence range of 12–97% among medical students, our study’s prevalence falls within the lower range 2 . Notably, our prevalence is lower than those reported in studies from China (74.3%), India (77.5%), Egypt (86.0%), and Sudan medical schools (94.5%) 9 , 12 14 , but higher than a study from Japan 12 . This difference may be attributed to variations in diagnostic methods and tools used to diagnose CVS.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations